2014
DOI: 10.1097/jan.0000000000000018
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol and Health Content in Nursing Baccalaureate Degree Curricula

Abstract: Globally, a paradigm shift has occurred in the field of alcohol and health from treatment of alcoholism to reducing at-risk drinking. The purpose of this study was to determine if schools of nursing include content reflective of the new paradigm in their Bachelor of Science in Nursing curricula. This was a cross-sectional electronic survey of schools of nursing to determine the mean number of alcohol-related content hours presented, the content offered, and the inclusion of strategies aimed at reduction of at-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 18 publications
2
23
0
1
Order By: Relevance
“…25,26 Despite paradigm shifts in public health, the nature of alcohol education within nursing courses still tends to focus most heavily on the treatment of alcohol dependence, with 1 study showing only 10% of schools required competency in screening or brief interventions to reduce high-risk drinking. 1,2,14,16 Although nursing students have high levels of knowledge about alcohol abuse prevention, our findings reinforce previous research suggesting that this knowledge does not translate to personal behavior change and more responsible drinking. 10,11 Waiting until students are accepted into nursing programs to begin aggressive alcohol abuse prevention strategies may be suboptimal.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…25,26 Despite paradigm shifts in public health, the nature of alcohol education within nursing courses still tends to focus most heavily on the treatment of alcohol dependence, with 1 study showing only 10% of schools required competency in screening or brief interventions to reduce high-risk drinking. 1,2,14,16 Although nursing students have high levels of knowledge about alcohol abuse prevention, our findings reinforce previous research suggesting that this knowledge does not translate to personal behavior change and more responsible drinking. 10,11 Waiting until students are accepted into nursing programs to begin aggressive alcohol abuse prevention strategies may be suboptimal.…”
Section: Discussionsupporting
confidence: 90%
“…These educational efforts frequently increase knowledge but are often inadequate to affect behavior change. [10][11][12][13][14][15] Although there is a need for nurse educators to reconsider the way they teach prevention and intervention strategies, 16,17 part of the issue with persistent alcohol abuse among nursing students may be that drinking patterns are well formed before entering nursing courses especially in programs that do not directly admit students. The purpose of this study is to determine if the drinking patterns of students admitted to a nursing program after a year of prerequisites differed from those of other female undergraduate students.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, in the United States, nurses are ill-prepared to address the needs of patients with at-risk alcohol use. A study by Savage, Dyehouse, and Marcus (2014) found that the mean number of contact hours related to alcohol and health in Baccalaureate nursing school curricula was 11.3 hours, with a range of 3 to 38 hours. Additionally, only 10% of the schools that responded to the survey reported that they evaluated students on their competency to deliver screening, brief intervention, and referral to treatment (Savage et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Some reasons for the lack of inclusion of substance use education may be due to concerns that the curriculum is an already oversaturated; assumptions that substance use is being taught in the psychiatric nursing or other courses; or that faculty do not have proficiency to teach the subject matter (Smothers et al, 2018). Nurses are the health care employees who have the most contact with patients, which places them in an ideal position to screen for substance use (Knopf-Amelung et al, 2018;Nash et al, 2017;Oermann, 2018;Savage, Dyehouse, & Marcus, 2014), and providing undergraduate nursing students' with substance use education has been found to build their confidence and competence, as well as reduce stigmatizing attitudes (Koetting & Freed, 2017;Lewis & Jarvis, 2019;Mahmoud et al, 2018;Nash et al, 2017;Smothers et al, 2018). There is evidence that some undergraduate programs have introduced substance use education classes and programs; however, these efforts are lacking consistency and it is not known what other substance useerelated content may be included (SBIRT [Screening, Brief Intervention, and Referral to Treatment]; alcohol, tobacco, pain management; stigma; or special populations), how many hours are included, or where in the curriculum the education occurs.…”
Section: Addiction-related Contentmentioning
confidence: 99%